2020
DOI: 10.7759/cureus.7711
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Bacterial Peritonitis: We Are Still Behind

Abstract: Spontaneous bacterial peritonitis (SBP) is an infection in the ascitic fluid. Despite published guidelines, an inappropriate diagnosis of SBP is frequent. In this study, we aim to evaluate guideline adherence in diagnosing SBP. This is a retrospective study conducted between January 2015 and January 2018. Based on the American Association for the Study of Liver Diseases (AASLD) and the European Association for the Study of Liver (EASL), two authors judged guideline adherence in SBP diagnosis and management. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…SBP is described as formation of infection in the abdominal cavity and a clear of source of infection is not known usually. 1,2 SBP occurs frequently among patients of portal hypertension which is commonly due to liver cirrhosis. 3 Patients having nephrotic syndrome are also prone to increased risk of SBP.…”
Section: Introductionmentioning
confidence: 99%
“…SBP is described as formation of infection in the abdominal cavity and a clear of source of infection is not known usually. 1,2 SBP occurs frequently among patients of portal hypertension which is commonly due to liver cirrhosis. 3 Patients having nephrotic syndrome are also prone to increased risk of SBP.…”
Section: Introductionmentioning
confidence: 99%
“…There is a variant in which the PMN value is <250 mm 3 , but with present culture called monomicrobial bacterascitis (4). Despite the diagnostic and treatment recommendations in the guideline, in a retrospective study made in the USA, only 52.4% of patients diagnosed with SBP met the criteria and only 67.3% of patients received appropriate treatment (5). The diagnostic challenge lies in the fact that the symptomatology of patients with SBP varies from typical symptoms to their partial or complete absence.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the prognosis of SBP has improved considerably due to effective antibiotic treatment; however, the mortality rate remains as high as 30% [11]. Patients with cirrhosis have immune dysfunction [12]. Delayed diagnosis of SBP leads to rapid disease progression and further deterioration of immune function, which leads to decreased effectiveness of antibiotic therapy.…”
Section: Spontaneous Bacterial Peritonitis (Sbp) Is the Most Common I...mentioning
confidence: 99%
“…According to the European guidelines, SBP is diagnosed based on a polymorphonuclear (PMN) leukocyte count ≥ 250 /mm 3 in ascetic uid and exclusion of secondary causes of intraabdominal infection. A retrospective study from the United States found that only 52.4% of SBP patients ful lled the PMN diagnostic criteria [12]. In addition, abdominocentesis is required to determine the ascitic uid PMN count.…”
Section: Spontaneous Bacterial Peritonitis (Sbp) Is the Most Common I...mentioning
confidence: 99%
See 1 more Smart Citation